2017
DOI: 10.1245/s10434-017-6087-9
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Gastrointestinal Stromal Tumor (GIST) in the Era of Imatinib: Organ Preservation and Improved Oncologic Outcome

Abstract: INTRODUCTION About 5% of GISTs originate in the rectum and historically radical resection was commonly performed. Little is known about the outcome of rectal GIST in the era of imatinib. METHODS Using a prospectively maintained database, we retrospectively analyzed 47 localized, primary rectal GISTs treated at our center from 1982 to 2016, stratified by when imatinib became available in 2000. Overall, disease-specific, and recurrence-free survival (OS, DSS, and RFS) were analyzed by the Kaplan-Meier method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 32 publications
(59 reference statements)
7
68
4
2
Order By: Relevance
“…Yasui et al found that rectal GISTs frequently recur and most often in a locoregional distribution. Thus, perioperative imatinib has been shown to be effective in reducing locoregional and distant recurrences after tumor resection, even in patients with positive margins . More recently, imatinib has been studied as a neoadjuvant treatment before surgery to reduce tumor burden and aid in operative success .…”
Section: Introductionmentioning
confidence: 99%
“…Yasui et al found that rectal GISTs frequently recur and most often in a locoregional distribution. Thus, perioperative imatinib has been shown to be effective in reducing locoregional and distant recurrences after tumor resection, even in patients with positive margins . More recently, imatinib has been studied as a neoadjuvant treatment before surgery to reduce tumor burden and aid in operative success .…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant IM can facilitate sphincter preservation in certain rectal GISTs. Indeed, patients with GISTs in all of these sites have been commonly selected for neoadjuvant treatment in retrospective series …”
Section: When Should Neoadjuvant Therapy Be Used?mentioning
confidence: 99%
“…Typically, neoadjuvant IM is used to facilitate a sphincter‐preserving operation and avoid an abdominoperineal resection and permanent end colostomy. A full‐thickness resection of the rectal wall is desirable and may sometimes be performed via the transanal approach if distal enough …”
Section: What Are the Technical Considerations For Specific Resections?mentioning
confidence: 99%
See 2 more Smart Citations